Using LLM for Mining and Testing Constraints in API Testing - Huynh, Minh-Hieu; Le, Quoc-Tri; Nguyen, Tien N.; Nguyen, Vu (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2024)
CCS Concepts* Software and its engineering → Software testing and debugging